Sensitivity of Different Developmental Stages and Resistance Risk Assessment of Phytophthora capsici to Fluopicolide in China - Wu, Jie; Xue, Zhaolin; Miao, Jianqiang; Zhang, Fan; Gao, Xiang; Liu, Xili (Frontiers in Microbiology, 2020)
Sensitivities of Phytophthora capsici to fluopicolide were investigated in vitro, with results showing that fluopicolide had strong inhibitory activities on each development stage of P. capsici, in particular on the motility of zoospore. The potential resistance risk for fluopicolide in P. capsici was evaluated. The baseline sensitivities to fluopicolide of 146 isolates obtained from 28 provinces in China were initially determined, and the 50% inhibition of mycelial growth (EC50) distribution was a unimodal curve with a mean of 0.17 µg/mL. A series of fluopicolide-resistant mutants of P. capsici were obtained by fungicide adaption and their biological traits determined. Most of the resistant mutants showed similar favorable fitness in mycelial growth, sporangium and zoospore production, cystospore germination, and pathogenicity compared with their sensitive parents, with few exceptions. Additionally, the cross-resistance result indicated that the sensitivity of fluopicolide did not correlate with other oomycete fungicides, apart from fluopimomide (LH-2010A). These results suggest a moderate to high resistance risk of P. capsici to fluopicolide in China.